Potencial Evocado Miogênico Vestibular Cervical e Ocular em indivíduos com Vestibulopatia Periférica Deficitária Unilateral e em indivíduos com Doença de Méniére - Tatiana Rocha Silva (2016)
Introduction: The vestibular evoked myogenic potential is a middle latency potential that measures the muscle response due to auditory stimulation. This potential can be generated from the contraction of the sternocleidomastoid muscle and also from the contraction of extraocular muscles in response to auditory high intensity sound stimulation. This study presents a combined or simultaneous technique of cervical and ocular vestibular evoked myogenic potential in individuals with desorders in the vestibular system in order to use in otoneurological diagnosis. Purpose: Evaluate the recordings and analyze the results of the combined cervical and ocular vestibular evoked myogenic potential in individuals with unilateral deficitary peripheral vestibulopathy and in individuals with Ménière's disease. Methods: This research was characterized by a study of descriptive typology, qualitative and quantitative analysis. 120 subjects were invited to participate in the study. The sample was composed of a study group of 30 individuals diagnosed of unilateral deficitary peripheral vestibulopathy and by 30 individuals with definite Ménière's disease. The control group was formed by 60 individuals without diagnosis of peripheral disorders of the inner ear. To record the combined cervical and ocular vestibular evoked myogenic potential a 100 stimulus at a frequency of 500 Hz tone burst were used at an intensity of 120 dBnHL with band pass filter 10 to 1.500 Hz, 50 ms recording time. Results: Difference was observed between the study group and the control group for the majority of wave parameters in the combined cervical and ocular vestibular evoked myogenic potential. In the study group there was no difference between the right and left ears. However, the combined cervical and ocular vestibular evoked myogenic potential presented altered responses in the asymptomatic ears of the individuals in the study group. Conclusion: The simultaneus recordings of the cervical and ocular vestibular evoked myogenic potential presented consistent results for latency and amplitude. The simultaneus cervical and ocular vestibular evoked myogenic potential may be used in the evaluation of the unilateral deficitary peripheral vestibulopathy and the Ménière's disease